Catalyst-Layer Ionomer Imaging of Fuel Cells. (14th September 2015) - Guetaz, Laure; Lopez-Haro, Miguel; Escribano, Sylvie; Morin, Arnaud; Gebel, Gerard; Cullen, David A.; More, Karren L.; Borup, Rod L
Abstract : Investigation of membrane/electrode assembly (MEA) microstructure has become an essential step to optimize the MEA components and manufacturing processes or to study the MEA degradation. For these investigations, transmission electron microscopy (TEM) is a tool of choice as it provides direct imaging of the different components. TEM is then widely used for analyzing the catalyst nanoparticles and their carbon support. However, the ionomer inside the electrode is more difficult to be imaged. The difficulties come from the fact that the ionomer forms an ultrathin layer surrounding the carbon particles and in addition, these two components, having similar density, present no difference in contrast. In this work, we show how the recent progresses in TEM techniques as spherical aberration (Cs) corrected HRTEM, electron tomography and X-EDS elemental mapping provide new possibilities for imaging this ionomer network and consequently to study its degradation.